The aliens inside human DNA: HERV-W/MSRV/syncytin-1 endogenous retroviruses and neurodegeneration - Antonina Dolei; Elena Uleri; Gabriele Ibba; Maurizio Caocci; Claudia Piu; Caterina Serra (Journal of Infection in Developing Countries)
The human genome contains remnants of ancestral retroviruses now endogenously transmitted, called human endogenous retroviruses (HERVs). HERVs can be variably expressed, and both beneficial and detrimental effects have described. This review focuses on the MSRV and syncytin-1 HERV-W elements in relationship to neurodegeneration in view of their neuro-pathogenic and immune-pathogenic properties. Multiple sclerosis (MS) and a neurodegenerative disease (neuroAIDS) are reported in this review. In vivo studies in patients and controls for molecular epidemiology and follow-up studies are reviewed, along with in vitro cellular studies of the effects of treatments and of molecular mechanisms. HERV-W/MSRV has been repeatedly found in MS patients (in blood, spinal fluid, and brain samples), and MRSV presence/load strikingly parallels MS stages and active/remission phases, as well as therapy outcome. The DNA of MS patients has increased MSRVenv copies, while syncytin-1 copies are unchanged in controls. Presence of MSRV in the spinal fluid predicted the worst MS progression, ten years in advance. The Epstein-Barr virus (EBV) activates HERV-W/MSRV both in vitro and in vivo. With respect to neuroAIDS, the HIV transactivator of transcription (Tat) protein activates HERV-W/MSRV in monocytes/macrophages and astrocytes indirectly by interaction with TLR4 and induction of TNFa. HERV-W/MSRV can be considered a biomarker for MS behavior and therapy outcome. Regarding MS pathogenesis, we postulate the possibility for EBV of an initial trigger of future MS, years later, and for MSRV of a direct role of effector of neuropathogenesis during MS. Additionally, HERV-W/MSR/syncytin-1 activation by HIV Tat could contribute to the HIV-related neurodegeneration.